Do Sanitary Pads Improve Girls' Educational Outcomes? - Agarwal, Sumit; Chia, Liu Ee; Ghosh, Pulak (The Review of Economics and Statistics, 2024)
Using a staggered installation of sanitary pad vending machines across schools in the Indian state of Kerala, we study the impacts of free monthly access to sanitary pads on girls' educational outcomes. We find that the number of dropouts among female students in the 7th-grade decrease by 24 percentage points and the attendance rate increases by 23 percentage points after the treatment. Our results are mainly driven by girls in backward-caste, rural schools, and public schools, supporting the idea that free distribution of sanitary pads alleviates cost of obtaining sanitary pads.